Determinan Laporan Pelaksanaan Anggaran Pendapatan Belanja Daerah - Khodijah Ishak; Kurniatul Fil Khoirin; Brilianza Indra Pratama; Muhammad Isa Selamat; Muhammad Fadhil Junery (LPPM ISNJ Bengkalis, 2022)
This study aims to analyze the effect of participation, clarity of targets, and budget feedback on the implementation report of the Bengkalis district revenue and expenditure budget (REB). This type of research is quantitative, with primary data in the form of a questionnaire. The population of this study was all elements of the regional secretariat of the Bengkalis district. The sampling technique used purposive sampling so that 60 samples were obtained. The data analysis technique used multiple linear regression with the help of SPPS 25 software. The results showed that participation and clarity of budget targets positively and significantly affected reports on implementing the Bengkalis district REB. Budget feedback does not affect reports on the implementation of the Bengkalis district REB. This research can be used as reference material for further research and the Bengkalis district government reporting the implementation of the REB.